O редакциях церковнославянского Пролога - Чистякова, Марина Владимировна Владимировна (Slavistica Vilnensis, 2013)
В статье уточнена и дополнена общепринятая классификация разновидностей церковнославянского Пролога: указаны краткие или расширенные варианты ранее выделенных редакций, стишные разновидности Простого пролога; в научный оборот впервые ввoдятcя киево-софийская редакция Простого пролога и рифмованная редакция Стишного пролога. В статье отмечены комбинированные прологи, в которых отдельные части рукописи отражают разные редакции, а также прологи, составленные путем контаминации разных редакций в один текст. Ключевые слова: cредневековая литература, кириллические рукописи, текстология, источниковедение, агиография, календарные четьи сборники, церковнославянский Пролог. ... Marina Chiststiakova About the editions of the Chuch Slavonic Synaxarion The Chuch Slavonic Synaxarion is an Orthodox calendar florilegium containing the lives of the saints and sermons. Characterised by a complex and extensive textual structure, the Synaxarion was widespread among the Eastern and Southern Slavic nations. Progressive studies into manuscripts have led to the discovery of new facts pertaining to the history of the Synaxarion text. This article summarises the observations made during the study into the editions of the Simple and Versed Synaxarion, which allowed clarifying and supplementing the existing classification of the editions. The article looks into the following main editions of the Simple Synaxarion: the Slavonic Synaxarion, the Kiev St. Sophia’s Cathedral edition, the Short and the Expanded editions, the Pskov edition, the Navahrudak edition and the following editions of the Versed Synaxarion: Tarnovo, Varlaam, Novgorod, Moscow, St. Cyril’s of White Lake Monastery edition, and the Rhymed edition. A more detailed classification includes short and expanded variants of these editions, versed versions of the Simple Synaxarion, and copies containing a mixed text of various editions.